Efficiency Improvement of Truck Queuing System in the Freight Unloading Process Case Study of a Private Port in Songkhla Province - Woottichaiwat, Sujin (Science, Engineering and Health Studies, 2015)
This study aimed to improve the efficiency of queuing system of supply trucks in freight unloadingprocess in a private port in Songkhla province. In everyday, suppliers delivered 5 types of supply to the port,including (1) oil-rig spare parts, (2) consumer products, (3) tools and chemicals, (4) helicopter fuel, and (5)plastic bins. Each truck consumed unequal operation time. The operation process was improved by methodanalysis and ECRS technique. Then, several models of truck scheduling were compared using Monte Carlosimulation technique. The models composed of first-come, first served (FCFS), shortest process time (SPT),longest processing time (LPT), and analytic hierarchy process (AHP) of both original (O) and new improved(N) processes. The result showed that New Longest Processing Time (NLPT) was the most efficient model,which reduced 77.2% in mean waiting time, decreased 69.0% in mean total time in system, and improvedfrom 11.94% to 35.30% in system utilization.